PENGARUH DANA BAGI HASIL, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP PENDAPATAN PERKAPITA PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI KALIMANTAN SELATAN TAHUN 2010-2013 - Ida Mentayani; Rusmanto Rusmanto; Lidya Selfia (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, This research aimed to examine the effect of Revenue Sharing Fund, General Allocation Fund, and the Special Allocation Fund To Income per capita for allegedly revenue sharing fund, General Allocation Fund, and the Special Allocation Fund affect per capita income in the District / City in the province of South Kalimantan. The population in this study was 13 (thirteen) District/City in South Kalimantan province from 2010-2013. Based on the criteria for purposive sampling method, obtained a sample of 9 (nine) District/City in the province of South Kalimantan. Data collection techniques done by documentation. Methods of data analysis using simple linear regression model multiple. The results showed that based on results of ANOVA test to obtain results that simultaneous revenue sharing, General Allocation Fund and Special Allocation Fund effect on per capita income with a significance level of 0.000. Partially indicates that the variable General Allocation Fund no effect on per capita income with a significance level of 0.123, the General Allocation Fund effect on per capita income with a significance level of 0.000, and the Special Allocation Fund has no effect on per capita income with a significance level of 0.117.